FACTORS THAT AFFECTING STUDENT'S LEARNING READINESS IN CLINICAL PRACTICE - Vita Purnamasari; Aris Setyawan (Universitas Respati Yogyakarta, 2021)
Quality education process will support the implementation of quality health services, anesthesia nursing education is education in which clinical learning is one of the learning processes. Student readiness is needed to undergo clinical practice so that competence can be achieved. Student readiness is influenced by several factors that can affect the clinical learning process. The general objective of this study was to identify emotional, psychological and knowledge factors related to the clinical practice readiness of anesthesiology nursing students at UNISA Yogyakarta. This research is a descriptive analytic study that will be conducted at the University of 'Aisyiyah Yogyakarta. The sample technique is purposive sampling technique during August 2020 - October 2020. The analysis test that will be used is Kruskal-Wallis Test. The results showed that emotional factors (P = 0.011), psychological factors (P = 0.03) and knowledge (P = 0.04) were factors that influenced students' clinical practice readiness. The conclusion this research is the factors that influence the readiness of students' clinical practice are emotional factors, psychological factors and knowledge factors. Keywords: Learning Readiness; Clinical Practice; Student